2006
DOI: 10.1097/01.mph.0000212915.22265.3b
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Study of Iron Accumulation in Liver, Myocardium, and Pituitary Assessed With MRI in Young Thalassemic Patients

Abstract: Clinical complications resulting from unevenly iron accumulation in individual organs of patients with beta-thalassemia major can affect both expectancy and quality of life. Magnetic resonance imaging (MRI) offers a quantitative, noninvasive, accurate method for estimating iron levels in various tissues, not easily accessible with other techniques. The aim of this study was to evaluate and correlate the level of iron accumulation in different organs (anterior pituitary, myocardium, and liver) assessed with MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 19 publications
4
41
1
2
Order By: Relevance
“…This needs to be further assessed by larger prospective studies based on repeated measurements of TSAT. Elisabetta Defraia, 4 Carlo Dessì, 4 Maria Loreta Foschini, 4 Nicolina Giagu, 4 Giovan Battista Leoni, 4 Maddalena Morittu, 4 and Renzo Galanello …”
Section: -14mentioning
confidence: 99%
See 1 more Smart Citation
“…This needs to be further assessed by larger prospective studies based on repeated measurements of TSAT. Elisabetta Defraia, 4 Carlo Dessì, 4 Maria Loreta Foschini, 4 Nicolina Giagu, 4 Giovan Battista Leoni, 4 Maddalena Morittu, 4 and Renzo Galanello …”
Section: -14mentioning
confidence: 99%
“…1 However, in nonchronically-transfused thalassemia patients, ferritin hepatosecretion does not match liver iron accumulation and neither is serum ferritin representative of extrahepatic siderosis. [1][2][3][4] These inherent limitations in viewing serum ferritin as a reliable marker of iron overload have led us to consider other plasma factors that might be more pertinent to the etiopathology of iron overload and relevant for initiating treatment and assessing its long-term efficacy. 5 Here, we considered labile plasma iron (LPI), the major redox-active and readily chelatable fraction of non-transferrin-bound iron (NTBI), as a more direct marker of impending tissue iron overload and, therefore, as a potential indicator for the initiation of chelation therapy.…”
mentioning
confidence: 99%
“…This knowledge could be applied to thalassemia patients when average iron levels in the liver exceeds a certain threshold. 41,42 In these cases, increased etheno-DNA adducts would be expected to be formed in the liver.…”
Section: Random Generation Of Eda In All Liver Cell Nucleimentioning
confidence: 99%
“…There was no correlation between serum ferritin levels and either with urinary εdA and εdC or with serum NTBI. Recent studies by the magnetic resonance imaging showed that the total tissue iron does not reflected by serum ferritin alone [20,21]. Total body DNA adducts which are formed in any tissue in the body are excreted in urine after DNA repair.…”
Section: Discussionmentioning
confidence: 99%